Citizen science in information systems research : evidence from a systematic literature review - Mäkipää, Juho-Pekka; Dang, Duong; Mäenpää, Teemu; Pasanen, Tomi (My University, 2020)
Citizen science refers to partnerships between scientists and the public in scientiﬁc research. Citizen science is considered as an emerging approach for conducting research in the field of information systems (IS). However, there is a fragmented understanding of citizen science in the IS community. As a result, we conducted a systematic literature review on citizen science in IS field aiming at understanding what and how IS scholars view and conduct their research related to citizen science. We searched papers from the database of the basket of eight senior journals, 47 SIG recommended journals by the Association for Information Systems, and the proceedings of five major conferences in IS including ICIS, ECIS, HICSS, PACIS, and AMCIS. Our findings provide the current status of citizen science research in IS field, such as how scholars view about citizen science, how to set up a citizen science project, or how citizen science is adopted in IS community. This research also contributes to the field by laying out suggestions for the future research of citizen science.
Keywords: 2020 Vision of Crowd Science; citizen science; data-quality; systematic literature review; user-generated content; fi=Tietotekniikka|en=Computer Science|